SARS-CoV-2 monoclonal antibody testing in vivo - Diamond, Michael (Henry Stewart Talks, 2021)
Work done in the lab to test monoclonal antibody efficacy in vivo, How the antibodies are chosen for testing, Work done on possible future SARS-CoV-2 mutations, Combating neutralisation escape, Working towards broadly neutralising antibodies, Future work for this research